2015
DOI: 10.1088/0953-8984/27/43/435702
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boron vacancies on phase stability, bonding and structure ofMB2(M  =  Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W) with AlB2type structure

Abstract: Transition metal diborides in hexagonal AlB2 type structure typically form stable MB2 phases for group IV elements (M = Ti, Zr, Hf). For group V (M = V, Nb, Ta) and group VI (M = Cr, Mo, W) the stability is reduced and an alternative rhombohedral MB2 structure becomes more stable. In this work we investigate the effect of vacancies on the B-site in hexagonal MB2 and its influence on the phase stability and the structure for 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
7
23
0
Order By: Relevance
“…[65,66] In order to observe the trend better, the ∆H is plotted with respect to transition metals in Figure 2 Despite the experimental synthesis of Ru 3 Al 2 B 2 , [46] the calculated ∆H is a relatively high positive value (0.07 eV/atom). This might imply that either our exchangecorrelation function for Ru is not appropriate or this compound could be formed experimentally because of the influences of vibrational entropy at high temperature and/or boron vacancies entropy effects [67]. According to the recent computational screening on inorganic crystal structure database (ICSD), [68] 20% of all compounds have instability of ∆H larger than 0.036 eV/atom.…”
Section: A Stabilities Of Mab Phasesmentioning
confidence: 99%
“…[65,66] In order to observe the trend better, the ∆H is plotted with respect to transition metals in Figure 2 Despite the experimental synthesis of Ru 3 Al 2 B 2 , [46] the calculated ∆H is a relatively high positive value (0.07 eV/atom). This might imply that either our exchangecorrelation function for Ru is not appropriate or this compound could be formed experimentally because of the influences of vibrational entropy at high temperature and/or boron vacancies entropy effects [67]. According to the recent computational screening on inorganic crystal structure database (ICSD), [68] 20% of all compounds have instability of ∆H larger than 0.036 eV/atom.…”
Section: A Stabilities Of Mab Phasesmentioning
confidence: 99%
“…On the other hand, in MgB 2 the peculiar self-doping exists thanks to the boron-related electrons at the Fermi level; at the same time also the s states of Mg donate their electrons to the boron-derived conduction bands (metallic B). It is also worth mentioning that B vacancies (a common defect occurring in diborides) enhance the DOS even further (more than twice for doping of about 0.5%) [8]. Besides the many similarities with MgB 2 , the lower T c values (7.31 and 8.33 K instead of 39 K) are accounted for by the differences in the electronic structure and Fermi surface.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum superconducting temperatures T c = 8.33 K and 7.31 K were reached in Zr 0.96 V 0.04 B 2 and Hf 0.97 V 0.03 B 2 , respectively, at the upper solubility limit of V (x ≈ 0.04). X-ray powder diffraction (XRD) patterns [7] indicate that an increase in V doping does not change the in-plane lattice parameter a, while it reduces the interlayer distance c. At the same time, it has been shown that the structural and electronic properties of these compounds are influenced by the presence of B vacancies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to many other ceramics, its resistivity is relatively low, which enables applications such as wear-resistant electrical contacts. While Zr-Zr-and Zr-B-bonds are strong and ionic/covalent in character, the B-Bbonds are significantly stronger whenever they can form a single sheet of hexagons [33,34], known as borophene (in analogy with graphene). This is possible for the AlB2-type structured materials (P6/mmm space group), to which ZrB2 belongs.…”
Section: Zrbmentioning
confidence: 99%